Correction to: Factors influencing the need for recovery in employees with hearing loss: a cross-sectional study of health administrative data - Hanneke E. M. van der Hoek-Snieders; Monique Boymans; Bas Sorgdrager; Wouter A. Dreschler (International Archives of Occupational and Environmental Health, 2020)

Factors influencing the need for recovery in employees with hearing loss: a cross-sectional study of health administrative data - Hanneke E. M. van der Hoek-Snieders; Monique Boymans; Bas Sorgdrager; Wouter A. Dreschler (International Archives of Occupational and Environmental Health, 2020)
Objective Need for recovery is a predictor of work stress and health problems, but its underlying factors are not yet well understood. We aimed to identify hearing-related, work-related, and personal factors influencing need for recovery in hearing-impaired employees. Methods We retrospectively identified hearing-impaired employees ( N = 294) that were referred to the Amsterdam University Medical Center between 2004 and 2019. Routinely obtained healthcare data were used, including a survey and hearing assessments. A directed acyclic graph was constructed, revealing the hypothesized structure of factors influencing need for recovery as well as the minimal set of factors needed for multiple regression analysis. Results Four variables were included in the regression analysis. In total, 46.1% of the variance in need for recovery was explained by the factors feeling that something should change at work ( B = 19.01, p < 0.001), self-perceived listening effort ( B = 1.84, p < 0.001), personal adaptations scale score ( B = − 0.34, p < .001), and having a moderate/poor general health condition ( B = 20.06, p < 0.001). Although degree of hearing loss was associated with self-perceived listening effort, the direct association between degree of hearing loss and need for recovery was not significant. Conclusions The results suggest that the way employees perceive their hearing loss and how they cope with it directly influence need for recovery, rather than their measured degree of hearing loss. Additionally, general health condition was found to be an independent factor for need for recovery. The results should be confirmed by future, longitudinal research.

Evaluation of the effectiveness of pre-employment screening - Bas Sorgdrager; Carel T. J. Hulshof; Frank J. H. van Dijk (International Archives of Occupational and Environmental Health, 2004)

Factors affecting FEV 1 in workers with potroom asthma after their removal from exposure - Bas Sorgdrager; Aart J. A. de Looff; Teake M. Pal; Frank J. H. van Dijk; Jan G. R. de Monchy (International Archives of Occupational and Environmental Health, 2000)

Occurrence of occupational asthma in aluminum potroom workers in relation to preventive measures - Bas Sorgdrager; Aart J. A. de Looff; Jan G. R. de Monchy; Teake M. Pal; A. Ewoud J. Dubois; Bert Rijcken (International Archives of Occupational and Environmental Health, 1998)